Importancia de la inclusión escolar en el proceso de enseñanza -aprendizaje en el tercer nivel de la Unidad Educativa “Jorge Icaza” de la parroquia Eloy Alfaro de la ciudad de Latagunga en el año lectivo 2015-2016 - Guaita León, Silvia Verónica (2016)
The following research work had as main objective: "To develop the importance of school inclusion in the process of teaching and learning in the third level of the Education Unit" Jorge Icaza "city of Latacunga," whose problem was the lack of educational inclusion, which affects teaching and learning in this educational establishment. the theoretical foundation and fundamental categories where aspects such as the educational community, school integration, inclusive education, school education, development of inductive schools and the teaching-learning, rinsed developed for which was used the descriptive methodology to determine whether the educational inclusion applies. The analysis and interpretation of the results of the interview to the director and the surveys to the teachers, students and parents were carried out, where she was known about the application of the educational inclusion in this establishment. The contribution of this thesis is in the proposal that is the development of a workshop to promote school inclusion in the educational unit "Jorge Icaza" of the city of Latacunga that allows the improvement of teaching learning.